De la intervención estatal excesiva a la regulación limitada en los aprovechamientos urbanísticos. Una aproximación alternativa al mercado inmobiliario (2018)
This paper focus on the city right’s concept and its effects. Today the Colombian government exhibits a growing intervention role in the market, despite its regulatory weakness. Local experts in urban planning have been using left social theories to justify that role, as a fixer of market’s inef-ficiencies and failures. State planning is usually considered the best way to guaranty the “common good”, while market is seen as a selfish and individualistic realm. Paradoxically politicians and its interventions generate the same inefficiencies attributed to market even worst. New libertarian perspectives show urban planning should be more specific regulation and less intervention on urban codes